Pesticides and Veterinary Drugs Residues in Conventional Meat: A Food Safety Issue - Khan, Irfan; Ahmad, Saghir (Journal of Buffalo Science, 2016)
In the current scenario the most of people are well aware with health issues. Food safety is generally related with the quality of food i.e. whether the food product is standardised as according to national or international norms set by the statutory organisations. People can compromise with the nutritive values of food but not with their safety aspects. The meat and meat products carry the burden of harmful agents according to the production methods. Now-a-days the feedlot animals are being reared either through the natural farming (organic farming) or conventional farming method. Those methods produce safe and healthier meat because there is no use of harmful chemical agents’ viz., pesticides, herbicides, hormones, growth promoters, veterinary drugs and etc. On the other hand, in the conventional farming, all these chemical agents are used to enhance animal growth. Several chemical agents like pesticides and veterinary drugs residues may cause harmful health implications viz., teratogenicity, carcinogenicity, hypersensitivity reactions, gut bacterial resistance, toxicity and many more health problems in human beings. It is the thrust of today to replace the conventional meat with the organic meat to check the use of harmful chemical agents for a healthy social life.